Optimalisasi Kinerja Terminal Dengan Menggunakan Metode Penilaian Tingkat Kepentingan Dan Kepuasan Pengguna Terminal (Studi Kasus Terminal Poris Pelawad Kota Tangerang) - Muhammadun, Haris (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
Terminal is the place for drop off and pick up of the people and transfer mode to next journey according trip end destination. The facility of terminal divided of vehicle facility, people facility, and operation facility. This facilities must be good performance, so can service the customer. But tf1e terminals officer, must be evaluation the facility conditions periodically. Importancei1erformance analysis method can be use, with interview the customer of terminal. Base on data from interview, percentage of importance level and satisfaction level can be measure. From this prercentage, problematic mapping shown for decided problem solving performance of terminal